2022
DOI: 10.3390/nano12234332
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Ti6Al4V-ELI Alloy with Antimicrobial Peptide Nisin

Abstract: Implant-associated infections are a severe global concern, especially in the case of orthopedic implants intended for long-term or permanent use. The traditional treatment through systemic antibiotic administration is often inefficient due to biofilm formation, and concerns regarding the development of highly resistant bacteria. Therefore, there is an unfulfilled need for antibiotic-free alternatives that could simultaneously support bone regeneration and prevent bacterial infection. This study aimed to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
2
8
2
Order By: Relevance
“…It can be assumed that the release is almost complete at this stage. This behavior is significantly different from that of polished and functionalized Ti6Al4V-ELI alloy as reported in [28] where the change in contact angle after the release test, compared to the functionalized surface, was lower in all cases. It can be concluded that the CT surface is able to release a larger amount of grafted nisin than the polished one; a role of physisorption instead of chemisorption in the different release can be supposed.…”
Section: Characterization After the Release Testscontrasting
confidence: 91%
See 4 more Smart Citations
“…It can be assumed that the release is almost complete at this stage. This behavior is significantly different from that of polished and functionalized Ti6Al4V-ELI alloy as reported in [28] where the change in contact angle after the release test, compared to the functionalized surface, was lower in all cases. It can be concluded that the CT surface is able to release a larger amount of grafted nisin than the polished one; a role of physisorption instead of chemisorption in the different release can be supposed.…”
Section: Characterization After the Release Testscontrasting
confidence: 91%
“…As last, the presence of calcium ions on the functionalized surfaces is in line with previous observations [31] and suggests that it has a role in the functionalization mechanism as a linker between the negatively charged functional groups of CT and nisin. This is different from what observed after functionalization with nisin of mechanical polished Ti6Al4V-ELI where the substrate has not such a high density of deprotonated functional groups and physisorption instead of chemisorption occurred [28].…”
Section: X-ray Photoelectron Spectroscopy (Xps)contrasting
confidence: 88%
See 3 more Smart Citations